Exploring forms of microaggression and coping mechanisms in schools experiences of transwomen college students - Faramiran, Zyreen Lou B ([Iloilo City] University of the Philippines Visayas, 2018)
Sexual minority groups live their lives surrounded by varying degrees of stressors which are unique to them as group. Lesbian, gay, bisexual and transgender youth (LGBT) continue to face extreme discrimination which may impact their mental health. this study explored the lived experiences of ten self-identified of transgender women college students from Iloilo City. specifically, the study focused on forms of microaggression experienced within the school context. Aspects of the Minority Stress Model (Meyer, 2003) were utilized to frame forms of microaggression experienced by transwomen students and how these may have outcomes in their mental health. Their interview responses were transcribed and thematically analyzed to generate specific themes from their lived experiences. Transwomen college students experience forms of microaggression in their microsystem environment such as transphobic language, sexual prejudice and directed disparaging behaviors. In their microsystem environment they experience generalized transgender experience, depreciated capacity and....
Special Problem (M.Ed. Guidance) -- University of the Philippines Visayas, June 2018.
Keywords: Transgender youth -- Research